Education policy and under-Five survival in Uganda: Evidence from the demographic and health surveys - Makate, Marshall (M D P I AG, 2016)
© 2016 by the author. This study seeks to examine the influence of mothers' schooling accomplishments on child mortality outcomes by exploiting the exogenous variability in schooling prompted by the 1997 universal primary education (UPE) policy in Uganda. The UPE policy, which eliminated school fees for all primary school children, provides an ideal setting for investigating the causal effect of the subsequent burst in primary school enrollment on child mortality outcomes in Uganda. The analysis relies on data from three waves of the nationally representative Uganda Demographic and Health Survey conducted in 2000/01, 2006, and 2011. To lessen the bias created by the endogenous nature of education, this study employs the mother's age at UPE implementation as an instrumental variable in the two-stage least squares model. The empirical analysis shows that one-year spent in school translates to a 2.24 percentage point decline in under-five mortality as observed at survey date and a 1.58 percentage point reduction in infant mortality even after accounting for potential confounding variables. These upshots are weakly robust to a variety of sample sizes and different model specifications. Overall, the results suggest that increasing the primary schooling possibilities for women might contribute towards a reduction in child mortality in low-income countries with high child mortality rates.